2001
DOI: 10.1177/0272431601021004005
|View full text |Cite
|
Sign up to set email alerts
|

Revised Description and Measurement of Ego Development in Early Adolescence:

Abstract: The applicability of the Loevinger conception of ego development was explored for the period of early adolescence. Recent modifications of the earliest ego levels are summarized, and a new version of the measure is presented: the Sentence Completion Test for Children and Youth (SCT-Y). Questions were considered about the reliability and validity of this new instrument. The main question addressed was whether an oral administration would yield essentially different responses and significantly differing ego-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 38 publications
(67 reference statements)
2
4
0
Order By: Relevance
“…Many studies have reported Cronbach's alpha values of .90 or higher. Similar reliability and internal consistency data were obtained for the SCT-Y (e.g., Westenberg, van Strien, & Drewes, 2001).…”
Section: Reliabilitysupporting
confidence: 75%
“…Many studies have reported Cronbach's alpha values of .90 or higher. Similar reliability and internal consistency data were obtained for the SCT-Y (e.g., Westenberg, van Strien, & Drewes, 2001).…”
Section: Reliabilitysupporting
confidence: 75%
“…Borderline rules were used to arrive at a total protocol rating (TPR) for each participant, with TPR scores corresponding to ego development levels (E2 to E9). The average ego level for the adolescents was near the conformity level ( M = 3.88, SD = 1.02), similar to a Dutch study of the same age group (Westenberg et al, 2001). The mothers’ protocols were scored in the same manner.…”
Section: Methodssupporting
confidence: 82%
“…Ego development consistently progresses with age during childhood and adolescence (Novy, 1993), but large variations in ego development have been found among age cohorts in individuals older than 14 (Redmore & Loevinger, 1979). The modal developmental stage for early adolescents in Dutch samples was between self-protective (E3) and conformist (E4) (Westenberg, van Strien, & Drewes, 2001). In Liu’s study (2009a, 2009b) of Taiwanese students, the average senior high school student had reached the conformist stage, and the average college student had reached the self-aware stage.…”
Section: Parent-child Interaction and Ego Developmentmentioning
confidence: 99%
“…These descriptive terms are applied to adults, children, and adolescents alike. However, recent efforts to collect extensive data on representative samples of children and adolescents by Westenberg and colleagues (Westenberg, Jonckheer, Treffers, & Drewes, 1998; Westenberg, Van Strien, & Drewes, 2001) suggest that the description of milestone characteristics for each stage in application to children and adolescents are likely to require revision. Although any person at the impulsive level of ego development may share similar conscious preoccupations, modes of handling impulses, and elements of interpersonal functioning, there are clearly different implications associated with this level of functioning in a 9‐year‐old child as compared with a 29‐year‐old adult.…”
Section: Ego Development Levels Characteristics and Milestones (Amentioning
confidence: 99%